Categories of Cutaneous Mosaicism - Rudolf Happle (JEADV Clinical Practice)
ABSTRACT In this overview, the following 12 different categories of cutaneous mosaicism are considered: (1) Discrimination between monoallelic and biallelic mosaicism in autosomal dominant traits; (2) Segmental versus disseminated mosaicism in autosomal dominant disorders. (3) Simple segmental versus superimposed mosaicism in autosomal dominant disorders. (4) Lethal mutations surviving in a mosaic; (5) Isolated segmental biallelic monoclonal mosaicism; (6) Autosomal recessive mosaicism; (7) Revertant mosaicism in autosomal dominant disorders; (8) Revertant mosaicism in autosomal recessive disorders; (9) Epigenetic mosaicism in X‐linked dominant, male‐lethal traits; (10) Epigenetic mosaicism in X‐linked, nonlethal traits; (11) Mosaicism in polygenic disorders; (12) Hypothetical epigenetic mosaicism in an autosomal dominant trait. Future research may show whether this classification is useful and complete.